387 Evaluating Intimate Partner Violence in pregnancy and stillbirths in a community setting in Pakistan. (1st September 2016) - Khatlani, Khaula; Azam, Iqbal; Baqir, Muhammad; Mehmood, Amber; Pasha, Omrana
Abstract : Background: Intimate partner violence (IPV) is a public health challenge and knowledge about relationship between intimate partner violence (IPV) during pregnancy and stillbirths is limited. We assessed the relationship of IPV during pregnancy and stillbirths, at a community level, in Pakistan. Methods: Using 1:2 case-control ratio, 256 cases (women delivering singleton stillbirths) and 539 controls (women delivering singleton, term live births) were selected from the Global Network for Women's and Children's Health Research Registry in Pakistan and individually matched on parity, in a matched, case-control community-based study. Trained female data collectors assessed IPV using WHO questionnaire "Multi-country Study on Women's Health and Life Experiences Questionnaire", between February and May 2014. Multivariable conditional logistic regression model determined the association between IPV in pregnancy and stillbirths, while adjusting for covariates. Results: The association of physical and psychological IPV in pregnancy with stillbirths was modified by maternal age. Women aged 25–34 years, delivering stillbirths, were 4 times more likely to experience physical IPV during index pregnancy, compared with their counterparts delivering live births (Matched adjusted odds ratio –MAOR = 4.1 [95% CI: 1.5–11.2]); after matching on parity and adjusting for women's education, working status, prior stillbirths, major antepartum haemorrhage, hypertensive disease, fetal malpresentation, obstructed/prolonged labour, severe pre-eclampsia/eclampsia, birth attendant and mode of delivery. Psychological IPV was negatively associated with stillbirths, in women younger than 25 years (MAOR = 0.2 [95% CI: 0.03–0.9]). Sexual IPV in pregnancy was not associated with stillbirths. Conclusions: Mid-reproductive age women delivering stillbirths, are more likely to experience physical IPV in pregnancy. Our findings are concerning and call for screening of women for violence during their antenatal visits.